597. Pharmacist-Led Interventions for Inpatient HIV-Related Medication Errors. (26th November 2018) - Wingler, Mary Joyce B; Stover, Kayla R; Barber, Katie E; Wagner, Jamie L
Abstract: Background: Inpatient HIV-related medication errors occur in up to 86% of patients. The purpose of this study was to evaluate the number of antiretroviral therapy (ART)- and opportunistic infection (OI)-related medication errors following the implementation of pharmacist-directed interventions. Methods: This quasi-experiment assessed adult patients with HIV who received ART, OI prophylaxis, or both from December 1, 2014 to February 28, 2017 (pre-intervention) or December 1, 2017 to February 28, 2018 (post-intervention). Pre-intervention patients were assessed retrospectively, verbal and written education were provided, then prospective audit and feedback was conducted for post-intervention patients. The primary outcome was rate of ART-related medication errors in the pre- vs. post-intervention groups. Secondary outcomes included time to resolution of ART- and OI-related medication errors, OI-related medication errors, types of errors, rate of acceptance of recommendations, in-hospital mortality, length of stay, and 30-day readmission. Results: Sixty-seven patients were included in each group (pre- and post-intervention). ART errors occurred in 44.8% and 32.8% ( P = 0.156), respectively. OI prophylaxis errors occurred in 11.9% vs. 9% ( P = 0.572), respectively. No difference was found in types of errors between groups, except medication omission decreased significantly in the post-intervention group (31.3% vs. 11.9%; P = 0.006). The number of pharmacist-based interventions increased in the post-intervention group (6.3% vs. 52.9%; P = 0.001). No statistical difference was found in average time to error resolution (72 vs. 48 hours; P = 0.123), but errors resolved during admission significantly increased (50% vs. 86.8%; P < 0.001). No difference was found in rate of intervention acceptance, which was high in both groups. Conclusion: In this quasi-experiment, ART and OI prophylaxis medication errors were numerically reduced in the pharmacist-led intervention period, and medication errors were resolved a day faster in the post-intervention period. Future interventions targeting prescribing errors upon admission include follow-up education and evaluation of medication reconciliation practices in HIV-infected patients. Disclosures: All authors: No reported disclosures.